GC- MS analysis of phytocomponents in leaves of Calamus Rotang - Y. PALLAVI,; K.P.J. HEMALATHA, (International Journal of Pharma and Bio Sciences, 2018)
The aim of the present study is to investigate the hexane and ethanolic leaf extracts of Calamus rotang for their phytochemical compounds using Gas chromatography- Mass spectroscopy. Phytochemical screening in leaves of Calamus rotang revealed the presence of some bioactive compounds. So GC-MS analysis was performed on a GC-MS equipment GC JEOL. GC-MS analysis in hexane leaf extract showed the presence of hexadecanoic acid methyl ester, octadecanoic acid methyl ester, phytol, eicosanoic acid methyl ester and GC-MS analysis in ethanolic leaf extract showed the presence of (E)-9-Octadecenoic acid ethyl ester, Octadecanoic acid ethyl ester, Pentadecanoic acid 13- methyl methyl ester, Hexadecanoic acid ethyl ester, 16- Octadecenoic acid methyl ester, Heptadecanoic acid 16-methyl-methyl ester. The presence of various bioactive components confirms the application of hexane and ethanolic leaf extracts in various diseases. However, isolation of individual phytocomponents may proceed to find a lead for herbal therapy.